2015
DOI: 10.1259/bjr.20140308
|View full text |Cite
|
Sign up to set email alerts
|

The potential of L-shell X-ray fluorescence CT (XFCT) for molecular imaging

Abstract: X-ray fluorescence CT (XFCT), a novel modality proposed for high-sensitivity high-resolution molecular imaging of probes labelled with a high atomic-number element, has been performed with high-energy K-shell X-rays. XFCT performed with low-energy L-shell X-rays could, in principle, result in an increase of XFCT imaging sensitivity; however, the significant L-shell X-ray attenuation limits its use for imaging of small objects. This commentary discusses the advantages and drawbacks of L-shell XFCT imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The authors claimed this was the highest sensitivity reported to date for a benchtop XRF-CT system and that the work formed the basis for signicant future improvements in sensitivity. Perhaps reecting the challenges for Au K line spectroscopy with tungsten target X-ray sources in XRF-CT, Bazalova-Carter 48 presented in a very readable commentary, the advantages and drawbacks of using L series XRF lines for such measurements. Although potentially high sensitivity could be expected for gold and platinum L series XRF lines, the Achilles heel remained the short penetrating depth of the XRF signals leading to the conclusion that such an approach would be limited to small animal CT.…”
Section: Laboratory Instruments and Excitation Sourcesmentioning
confidence: 99%
“…The authors claimed this was the highest sensitivity reported to date for a benchtop XRF-CT system and that the work formed the basis for signicant future improvements in sensitivity. Perhaps reecting the challenges for Au K line spectroscopy with tungsten target X-ray sources in XRF-CT, Bazalova-Carter 48 presented in a very readable commentary, the advantages and drawbacks of using L series XRF lines for such measurements. Although potentially high sensitivity could be expected for gold and platinum L series XRF lines, the Achilles heel remained the short penetrating depth of the XRF signals leading to the conclusion that such an approach would be limited to small animal CT.…”
Section: Laboratory Instruments and Excitation Sourcesmentioning
confidence: 99%
“…K-shell XFT enables imaging at larger depth in tissue. L-shell XFT can be used to image shallow tumors, but with higher detection sensitivity, due to increased photoelectric cross-section, reduced Compton scattering, and better detector energy resolution at lower energy (18)(19)(20). L-shell XFT has been verified by Monte Carlo simulation for its higher sensitivity (3.0-4.4 times better than K-shell imaging) in imaging small objects (21).…”
Section: Introductionmentioning
confidence: 99%
“…X -ray fluorescence computed tomography (XFCT) is a tomographic imaging modality known for its highsensitivity as well as its capacity of determining the distribution of sufficiently high atomic number elements inside the sample. 1 These two features have made it a popular imaging tool for the analysis of samples in numerous research fields. For instance, XFCT has been used to visualize the distribution of iron in biological samples, such as Arabidopsis seeds.…”
mentioning
confidence: 99%